Videolaparoscopic cholecystectomy. Experience on 386 cases - Weisburd, F J; Errera, R; Morganti, A.; Falco, F; Mele, F (Cirugía del Uruguay, 1994)
We have presented the experience of laparoscopic cholecystectomy wich has been done at Hospital Italiano de La Plata, from april 1991 until june 1993. From a total of 386 patients who were undergone surgery, 252 (65%) have presented gallstone symptons; 92 ofthen (23%) acute cholecystitis; 26 patients (7,5%) have presented mínima! hipertension billiary syndrome; 14 (4%) of then, have presented obstructive jaundice, and 2 patients (0,5%) with pancreatitis.